2016
DOI: 10.1177/1747954116684392
|View full text |Cite
|
Sign up to set email alerts
|

Psychological characteristics of champion orienteers: Should they be considered in talent identification and development?

Abstract: A range of cognitive skills that support the development of sport potential have been suggested to be important for athletes and coaches. This study explored performers' psychological characteristics within orienteers. The psychological skills of World Elite orienteers and athletes in the National Junior Squads of both Great Britain and Switzerland were assessed using the six factor Psychological Characteristics of Excellence Questionnaire. Data suggested that, as juniors, elite orienteers reported less suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…This may seem surprising given that qualitative studies have consistently shown imagery to be important for development into an elite senior athlete (Durand-Bush & Salmela, 2002;Gould, Dieffenbach, & Moffett 2002;MacNamara et al, 2010aMacNamara et al, , 2010b. However, despite the reduction in imagery use during practice and competition, the mean scores of U15-U16 players in the current study were similar or higher compared to elite youth and senior orienteers (Newton & Holmes, 2017) 3.89 ± 0.99, respectively). Therefore, elite youth football players aged 11-16 years engage in relatively high levels of imagery usage, suggesting that it may be useful in engaging in their current context, i.e., being a member of a professional academy.…”
Section: Resultscontrasting
confidence: 74%
See 3 more Smart Citations
“…This may seem surprising given that qualitative studies have consistently shown imagery to be important for development into an elite senior athlete (Durand-Bush & Salmela, 2002;Gould, Dieffenbach, & Moffett 2002;MacNamara et al, 2010aMacNamara et al, , 2010b. However, despite the reduction in imagery use during practice and competition, the mean scores of U15-U16 players in the current study were similar or higher compared to elite youth and senior orienteers (Newton & Holmes, 2017) 3.89 ± 0.99, respectively). Therefore, elite youth football players aged 11-16 years engage in relatively high levels of imagery usage, suggesting that it may be useful in engaging in their current context, i.e., being a member of a professional academy.…”
Section: Resultscontrasting
confidence: 74%
“…MacNamara and Collins (2013) showed that in elite youth team sports athletes aged 16, coach-rated 'good developers' displayed higher scores than 'poor developers' on evaluating performances and working on weaknesses (4.99 ± 0.72 vs. 4.56 ± 0.85). Furthermore, British elite youth orienteers scored particularly highly on this factor (4.97 ± 0.79), and in-depth interviews with their coaches revealed that it was a major focus of talent development processes in this context (Newton & Holmes, 2017). The current study is the first to provide evidence that this unique factor is important in the development of elite youth football players.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…To maximize the potential of the orienteer, the selection and training of orienteers are both important (Newton & Holmes, 2017). This finding reminds us that we should increase the familiarity of the orienteer with the map information during training.…”
Section: Discussionmentioning
confidence: 99%